The Spiritual Dimension of The Naqsyabandi Haqqani Order as a Da'wah Method in The Educational System of Al-Falah Islamic Boarding School Cicalengka Bandung - Anwar, Syuhudul; Feriyanto, Feriyanto; Risdayah, Enok; Aziz, Rohmanur; Setiawan, Asep Iwan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2025)
This study explores the spiritual dimension of the Naqsyabandi Haqqani Sufi Order as a da'wah method within the educational system of Al-Falah Islamic Boarding School in Cicalengka, Bandung. This Sufi order emphasizes dzikr (remembrance of God), self-restraint, and direct spiritual guidance from a mursyid (spiritual teacher) as foundational da'wah approaches for character development and Islamic propagation among santri. Using a descriptive qualitative approach, this research analyzes how spiritual values such as tawhid (divine unity), iman (faith), and sabr (patience) are integrated into formal and non-formal pesantren curricula as effective da'wah strategies. The findings reveal that the Naqsyabandi Haqqani spiritual dimension functions as a comprehensive da'wah method reflected in students' daily activities, consistently instilling Islamic values through direct and indirect propagation approaches. This da'wah-oriented spiritual development system produces academically competent, spiritually profound, and morally upright students while preparing them as future da'i (Islamic propagators). The Sufi spirituality serves as both moral foundation and da'wah methodology, strengthening Islamic education's goal of forming insan kamil (the complete human being) who embodies and propagates Islamic teachings. The study demonstrates that the Naqsyabandi Haqqani approach transforms traditional Islamic education into an active da'wah platform, where the pesantren becomes a living laboratory for Islamic propagation. Through this spiritual-based da'wah method, students experience profound transformation that cultivates their capacity for effective Islamic outreach. Thus, Al-Falah's educational system transmits knowledge, transforms souls, and nurtures committed da'wah agents who contribute to the broader Islamic mission in contemporary society.